2018
DOI: 10.2147/tcrm.s155358
|View full text |Cite
|
Sign up to set email alerts
|

The quantification and assessment of depression and anxiety in patients with postoperative gastroparesis syndrome

Abstract: BackgroundThis study aimed to analyze the stage-situation depression and anxiety as well as independent influential factors in patients with postsurgical gastroparesis syndrome (PGS) and to provide dependent indications for treatment.Patients and methodsThe self-rating depression scale (SDS) and self-rating anxiety scale (SAS) were used to test the depression and anxiety of 53 patients with PGS, who were treated in the Department of Gastroenterological Surgery of Gansu Provincial Hospital from January 2012 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In recent years, the departments of cardiovascular medicine, neurology and gastroenterology in general hospitals have become the popular departments for Chinese patients with emotional disorders to seek help outside the psychological center. [35][36][37][38][39] With the deepening understanding of emotional disorders, more and more scholars reported the emotional problems of cardiovascular outpatients or inpatients. [35][36][37] There are two types of patients with emotional disorders in the department of cardiovascular medicine.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the departments of cardiovascular medicine, neurology and gastroenterology in general hospitals have become the popular departments for Chinese patients with emotional disorders to seek help outside the psychological center. [35][36][37][38][39] With the deepening understanding of emotional disorders, more and more scholars reported the emotional problems of cardiovascular outpatients or inpatients. [35][36][37] There are two types of patients with emotional disorders in the department of cardiovascular medicine.…”
Section: Discussionmentioning
confidence: 99%
“…While ensuring the safety of surgery and postoperative recovery, the functional recovery of the digestive tract after reconstruction has become an essential component of shortterm postoperative recovery, which has attracted increasing attention from clinicians. Gastroplegia syndrome is considered one of the most common complications related to digestive tract function, with an incidence rate of approximately 2∼3% (34). The results of the study showed that the incidence of gastroparesis syndrome in the linear stapler group was much lower than that in the circular stapler group (3.2 vs. 6.2%, p = 0.561), but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 79%
“…The application in surgical oncology not only helps in reducing patients’ complications and facilitating their rehabilitation, but also plays an active role in helping medical staffs to change the traditional treatment thinking and nursing modes. SAS and SDS scales are characterized by a relatively wide application in clinical treatment and scientific research, high validity, good reliability, and simple and easy application; its contents involve emotional experience and emotion-related somatic symptoms, and these symptoms are relatively common in patients at the status post-open radical gastrectomy ( Lijuan et al ., 2018 ). Compared to the traditional open radical gastrectomyfor gastric cancer, Da Vinci robot-assisted radical gastrectomy for gastric cancer is characterized by small trauma, accurate surgical range, less intraoperative bleeding, early proper timing for postoperative food intake and high rate of lymphatic clearance ( Suda et al ., 2015 ), which makes the Da Vinci surgical system increasingly applied in radical gastrectomy.…”
Section: Discussionmentioning
confidence: 99%